From a Sociological Given Context to Changing Practice: Transforming Problematic Power Relations in Educational Organizations to Overcome Social Inequalities - Lémonie, Yannick; Grosstephan, Vincent; Tomás, Jean-Luc (Frontiers in Psychology, 2021)
In 2012, the international PISA survey reinforced the observation that the French educational system is one of the most unequal among OECD countries. The observation of serious inequalities in access to educational success for pupils from disadvantaged backgrounds could lead to a pessimistic vision suggesting that any possibility of transformation of the system is doomed to failure. Thus, the fight against inequalities in access to educational success is a form of runaway object which constitutes a challenge for research which treats the social context as evolving and susceptible to significant and novel transformations. Developmental work research aims to support the work of professionals in the re-elaboration of their practices by seeking to go beyond the status quo of an unequal school. Drawing on this framework within an institutional network of schools, we seek to show how the intervention has highlighted power issues inscribed in the structures and how the actors, through their commitment in the research collaborative process, seek to go beyond the power issues inscribed in their work routines and enacted during the research process by different kinds of antagonism. We will argue that the fight against educational inequality involves overcoming systemic power relations crystallized in institution. This systemic power is expressed by a form of episodic power. Our results show restrictive and constructive effect on the expansive learning process and on the construction of a collective in the formative interventions. The restrictive side of epistemic power should be linked to systemic power which is historically inherited. We discuss the results in the light of the emergence of a fourth generation of activity theory. Our research makes it possible to make conceptual and methodological progress in the construction of a fourth generation of activity theory by showing the need for analysis and expansively learn about problematic power relations in heterogeneous collectives.